2017
DOI: 10.3389/fimmu.2017.00808
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Early Infant Death Correlates with Earlier Age at Diagnosis But Not Shorter Time to Diagnosis for Severe Combined Immunodeficiency

Abstract: BackgroundSevere combined immunodeficiency (SCID) is fatal unless treated with hematopoietic stem cell transplant. Delay in diagnosis is common without newborn screening. Family history of infant death due to infection or known SCID (FH) has been associated with earlier diagnosis.ObjectiveThe aim of this study was to identify the clinical features that affect age at diagnosis (AD) and time to the diagnosis of SCID.MethodsFrom 2005 to 2016, 147 SCID patients were referred to the Asian Primary Immunodeficiency N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 66 publications
1
20
1
Order By: Relevance
“…In conclusion, the diagnosis of disseminated BCG disease should be considered when a BCG vaccinated infant presents with cutaneous papules, pustules, and nodules, especially in infants with immunodeficiency. One study from the Asian Primary Immunodeficiency Network found typical clinical features of SCID, like candidiasis, BCG infections, pneumonia, chronic diarrhea, severe infections, and absolute lymphocyte count below 3 × 109/L were often not recognized by clinicians, thereby prolonging the time to diagnosis . The only solution for early diagnosis of SCID is newborn screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the diagnosis of disseminated BCG disease should be considered when a BCG vaccinated infant presents with cutaneous papules, pustules, and nodules, especially in infants with immunodeficiency. One study from the Asian Primary Immunodeficiency Network found typical clinical features of SCID, like candidiasis, BCG infections, pneumonia, chronic diarrhea, severe infections, and absolute lymphocyte count below 3 × 109/L were often not recognized by clinicians, thereby prolonging the time to diagnosis . The only solution for early diagnosis of SCID is newborn screening.…”
Section: Discussionmentioning
confidence: 99%
“…One study from the Asian Primary Immunodeficiency Network found typical clinical features of SCID, like candidiasis, BCG infections, pneumonia, chronic diarrhea, severe infections, and absolute lymphocyte count below 3 × 109/L were often not recognized by clinicians, thereby prolonging the time to diagnosis. 11 The F I G U R E 4 Black arrow designates the proband. Sequencing identified de novo compound heterozygous mutation c. 1934 A > G in the JAK3 gene and heterozygous variant c. 1899 C > A in the JAK3 gene carried by both the proband and her mother…”
Section: Discussionmentioning
confidence: 99%
“…The SCIDX1 patients with IL2RG deficiency are the largest group in the populations with low‐consanguinity rates like European or far east countries (Fischer et al., 2015; Luk et al., 2017), but we found RAG1/2 deficiency (47%) which leads to T‐B‐NK+ phenotype is the most common group in our Turkish SCID cohort. Due to the high consanguineous marriage rates in our country, autosomal‐recessive inherited genes might be the most effected genes among the SCID patients in our cohort.…”
Section: Discussionmentioning
confidence: 45%
“…The R328X mutation was first reported in 2017 in a cohort of 147 Asiatic SCID patients , but detailed clinical and immunological information has only been described recently in two patients with the same mutation . Lim et al reported the R328X mutation in a 16‐year‐old Kurdish boy with chronic airway hypersensitivity and recurrent sinopulmonary infections and Tanita et al described the same mutation in a 21‐year‐old Japanese male with recurrent respiratory infections, EBV‐associated leiomyoma during childhood and invasive Haemophilus influenzae infection .…”
Section: Discussionmentioning
confidence: 99%
“…Until very recently, mutations in exon 8 have been described only in association with the typical X-SCID phenotype [28], thus suggesting a critical role on the C-terminal part of the cytoplasmic domain of γ c for correct signal transmission. Up to the present, two case reports and a cohort study have reported a hypomorphic mutation located in exon 8 (c.C982T/ p.328X) [19,21,29].…”
Section: Introductionmentioning
confidence: 90%